Hapus Perilaku Pelecehan Spiritual dalam Penanganan Kasus Perempuan Korban Perkosaan (Asosiasi Teolog Indonesia, 2014)
Incidents of rape are often broadcast on the news and other media. Although the frequency of reported rape need not equate to its being commonplace, there is a danger of desensitization. We're such conditioning to continue, women victims could be placed at greater risk for gender inequality. Pastors are in a special position, to execute the duties of priesthood and prophet (civic justice advocate), as part of an overall strategy of ministry to the community. But when a pastor does not play this role, perhaps due to the politics of influence and power vis-à-vis his or her position, in the analysis of the present author this should be regarded as spiritual abuse. Therefore, this paper considers the following proposal: such pastors must turn to reflect upon the nature of pastoral service and upon the attitude Jesus showed throughout his exemplary ministry. Only such reflection will combat the proclivity toward perpetuating the aforementioned spiritual abuse.